Global timing: a conceptual framework to investigate the neural basis of rhythm perception in humans and non-human species - Geiser, Eveline; Walker, Kerry M.; Bendor, Daniel (Frontiers in Psychology, 2014)
Timing cues are inarguably an essential feature of music. To understand how the brain gives rise to our experience of music we must appreciate how acoustical temporal patterns are integrated over the range of several seconds in order to extract global timing. In music perception, global timing comprises three distinct but often interacting percepts: temporal grouping, beat, and tempo. What directions may we take to further elucidate where and how the global timing of music is processed in the brain? The present review addresses this question and describes our current understanding of the neural basis of global timing perception.